Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Berbasis Ice Breaking Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Jannah, Miftahul; Husniati, Andi; Sirajuddin (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The purpose of this study was to find out how the influence of the Teams Games Tournament (TGT) learning model with the help of Ice Breaking on mathematics learning outcomes for third-grade students of SDN No. 113 Inpres Laikang. This research is experimental research (pre-experimental design) with a one-group pretest-posttest design. The population of this study was class III SDN No. 113 Inpres Laikang. The sample in this study was taken with a saturated sample technique, namely: all students of class III SDN No. 113 Inpres Laikang, totaling 16 people. The method of collecting data on mathematics learning outcomes uses the pretest and posttest test methods with the instrument questions in the form of essays and a questionnaire whose instruments are in the form of statements. Data on mathematics learning outcomes were analyzed using descriptive and inferential statistical analysis (t-test). The results showed that there was an increase in the mathematics learning outcomes of the third-grade students of SDN No. 113 Inpres Laikang after the implementation of the Teams Games Tournament (TGT) learning model assisted by Ice Breaking with the pretest results obtained an average value of 42.13 and at the time of the posttest the average value of 74.63 was in the high category and student responses were obtained with an average value average 81.25. while inferential statistical analysis using the t-test formula, the obtained significance value is 0.000 <0.05 so it can be concluded that this value can prove that H_o is rejected and H_1 is accepted. Based on the results of this study, there is an effect of applying the Teams Games Tournament (TGT) learning model assisted by Ice Breaking on the mathematics learning outcomes of third-grade students at SDN No. 113 Inpres Laikang.